A novel drivetrain modelling approach for real-time simulation. (December 2015) - Bachinger, Markus; Stolz, Michael; Horn, Martin
Abstract: This article opens perspectives for generic modelling and real-time simulation of automotive gear transmissions containing multiple friction elements. Generic mathematical drivetrain modelling is challenging, as friction elements cause a system to vary its order and structure. Furthermore, adaptive time-step methods are not suitable for real-time simulation. Unfortunately, literature lacks flexible fixed time-step approaches for multiple friction elements. The modelling solution proposed in this article is designed for fixed time-step execution and is applicable to all types of gear transmissions. The approach is verified on an exemplary simplified drivetrain. It is demonstrated on a complex hybrid-electric automatic drivetrain topology and validated via transmission test bench measurement. Finally, the approach is applied to a conventional automatic drivetrain and validated via vehicle measurement.